Both Orai1 and TRPC1 are Involved in Excessive Store-Operated Calcium Entry in Striatal Neurons Expressing Mutant Huntingtin Exon 1 - Vigont, Vladimir; Kolobkova, Yulia; Skopin, Anton; Zimina, Olga; Zenin, Valery; Glushankova, Lyuba; Kaznacheyeva, Elena (Frontiers in Physiology, 2015)
It has been previously reported that N-terminus of mutant huntingtin (product of the 1st exon) is sufficient to cause a Huntington’s disease (HD) pathological phenotype. In view of recent data suggesting that improper regulation of store-operated calcium (SOC) channels is involved in neurodegenerative processes, we investigated influence of expression of the mutant huntingtin N-terminal fragment (Htt138Q-1exon) on SOC entry (SOCE) in mouse neuroblastoma cells (Neuro-2a) and in primary culture of medium spiny neurons (MSNs) isolated from mice. The results show that SOCE in these cells is enhanced upon lentiviral expression of the Htt138Q-1exon. Moreover we demonstrated that RNAi-mediated knockdown of TRPC1, Orai1 or STIM1 proteins leads to dramatic reduction of abnormal SOCE in both Neuro-2a and MSNs, expressing Htt138Q-1exon. Thus we concluded that abnormal SOCE in these cells is maintained by both TRPC1- and Orai1-containing channels and required STIM1 for its activation. Furthermore, EVP4593 compound previously tested as a potential anti-HD drug in a Drosophila screening system has proved to be capable of reducing SOCE to the normal level in MSNs expressing the Htt138Q-1exon.